Segmentation of Heart Sound Signals into Cycles based on Peak Intervals Pattern - Ahmad Zubir Suboh (2015)
Heart sound segmentation was very important as it is one of the most important steps in heart sound analysis. This paper describes how heart sound signal is segmented into cycles based on the pattern of peak intervals. The major steps in this project include detecting the significant peaks, determining intervals consistency level and finally removing unwanted peak as well as recovering the missing peak. 908 out of 1089 cycles from 62 set of normal and abnormal signals are successfully detected by the system.